26. THE EFFECTIVENESS OF IMPROVING CERVICAL SPINE RANGE OF MOTION USING LASER ACUPUNCTURE COMBINED WITH EXERCISE THERAPY IN PATIENTS WITH CERVICAL SPONDYLOSIS (Tạp chí Y học Cộng đồng, 2024)
Objective: To evaluate the effectiveness of improving cervical spine range of motion (ROM) using laser acupuncture combined with exercise therapy in patients with cervical spondylosis.Subjects and Methods: The study was conducted on 30 patients diagnosed with cervical spondylosis (CS). All patients received laser acupuncture and exercise therapy for 4 weeks. The effectiveness was evaluated before and after treatment through cervical spine ROM.Results: After 4 weeks of treatment, cervical spine ROM improved in all 6 movements. The overall cervical spine motion limitation score decreased by 8 points, from 12 points to 4 points (p < 0.05). The distribution of motion limitation levels changed, with moderate limitation dropping from 70% to 13.33%, severe restriction from 10% to 0%, and an increase in the number of patients with mild or no limitations to 60% and 26.67%, respectively.Conclusion: The combination of laser acupuncture and exercise therapy in the treatment of cervical spondylosis effectively improves cervical spine ROM in patients.
Keywords: Laser acupuncture; exercise therapy; cervical spondylosis